Quantification of myocardial amyloid deposition in tafamidis-treated patients with transthyretin amyloid cardiomyopathy. (14th October 2021) - Rettl, R; Wollenweber, T; Mann, C; Duca, F; Dachs, T.-M; Binder, C; Stojanovic, M; Camuz Ligios, L; Schrutka, L; Dalos, D; Charwat-Resl, S; Badr Eslam, R; et al.
Abstract: Background: Tafamidis kinetically stabilizes the tetrameric form of transthyretin (TTR) and thus may halt disease progression in patients with transthyretin amyloid cardiomyopathy (ATTR-CM). However, the effect of tafamidis treatment on the progression of myocardial amyloid deposition is still unclear. Methods: In our explorative analysis, we aimed to investigate the treatment effect of tafamidis on myocardial amyloid deposition measured by myocardial standardized uptake value (SUV) peak and SUV retention index using quantitative single-photon emission computed tomography/computed tomography (SPECT/CT) of the thorax and to observe its association with clinical parameters. Therefore, clinical, laboratory, imaging, and SPECT/CT examinations were performed in twenty consecutive ATTR-CM patients who started treatment with tafamidis 61mg, both at baseline and at a median of 6 months. Results: Main results are summarized in Table 1. In brief, we observed a significant reduction of mean myocardial SUV peak (baseline: 15.50 vs. follow-up: 11.61, p<0.001) and mean SUV retention index (5.64 vs. 3.58, p=0.001) after treatment with tafamidis (Figure 1A). Interestingly, a higher percentage decrease in the SUV retention index is more likely to be associated with clinical benefit, with a threshold of −30% distinguishing between patients who respond clinically (n=12) and those who do not (n=8, Figure 1B). Clinical response is demonstrated by improvement in exertional dyspnea (NYHA class III: 83.3% vs. 41.7%, p=0.047) and mean functional capacity as measured by 6-minute walk distance (349.5m vs. 356.7m, p=0.736). Cardiac biomarkers analysis showed a clear reduction in median NT-proBNP levels in the responder cohort (2765.0 pg/mL vs. 1904.0 pg/mL, p=0.041) compared to an increase in the non-responder cohort (1825.0 pg/mL vs. 1944.0 pg/mL, p=0.208; cohort comparison: p=0.026, Figure 1C). Echocardiographic findings revealed improvement in mean left ventricular (LV) strain (−12.0% vs. −13.5%, p=0.049) and mean LV ejection fraction (LVEF, 48.5% vs. 52.7%, p=0.287) in the responder cohort, while significant deterioration in mean LV function (LV strain: −13.9 vs. −10.5, p=0.035; LVEF: 53.2% vs. 46.5%, p=0.012) was observed in the non-responder cohort, with an additional substantial deterioration in right ventricular (RV) function as measured by tricuspid annular plane systolic excursion (TAPSE, mean, BL: 19.2mm vs. FU: 12.6mm, p=0.037) in those patients. These results are consistent with changes in the LV and RV function in cardiac magnetic resonance imaging parameters in each of the two cohorts. Conclusion: Treatment with tafamidis in patients with ATTR-CM results in a significant reduction in myocardial amyloid deposition as measured by the SUV retention index, with a threshold of −30% distinguishing patients who respond clinically from those who do not. However, a larger patient sample is needed to verify these results. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Pfizer Inc.